Recent trends in the modification of polyphenolic compounds using hydroxylation and glycosylation - Lee, Uk Jae; Sohng, Jae Kyung; Kim, Byung Gee; Choi, Kwon Young (Current Opinion in Biotechnology, 2023)
Polyphenols are bioactive molecules that are used in therapeutics. Polyphenol hydroxylation and glycosylation have been shown to increase their bioavailability, solubility, bioactivity, and stability for use in various applications. Ortho-hydroxylation of polyphenols using tyrosinase allows high selectivity and yield without requiring a cofactor, while meta- and para-hydroxylation of polyphenols are mediated by site-specific hydroxylases and cytochrome P450s, although these processes are somewhat rare. O-glycosylation of polyphenols proceeds further after hydroxylation. The O-glycosylation reaction typically requires nucleotide diphosphate (NDP) sugar. However, amylosucrase (AS) has emerged as a promising enzyme for polyphenol glycosylation in large-scale production without requiring NDP-sugar. Overall, this review describes recent findings on the enzymatic mechanisms, enzyme engineering, and applications of enzymatic reactions.
Keywords: Bioactive molecules; Cofactors; Glycosylations; High selectivity; Higher yield; Meta-hydroxylation; O-glycosylation; Polyphenols; Recent trends; Site-specific; Carbohydrates; Cytochrome P-450 Enzyme System; Glycosylation; Hydroxylation; Polyphenols; Sugars